2023
DOI: 10.1007/s00018-022-04680-w
|View full text |Cite
|
Sign up to set email alerts
|

FHL3 promotes the formation of fast glycolytic muscle fibers by interacting with YY1 and muscle glycolytic metabolism

Abstract: The proportions of the various muscle ber types are important in the regulation of skeletal muscle metabolism, as well as animal meat production. Four-and-a-half LIM domain protein 3 (FHL3) is highly expressed in fast glycolytic muscle bers and differentially regulates the expression of myosin heavy chain (MyHC) isoforms at the cellular level. Whether FHL3 regulates the transformation of muscle ber types in vivo and the regulatory mechanism are unclear. In this study, muscle-speci c FHL3 transgenic mice were g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Moreover, consistent with these findings, the oxygen consumption was markedly decreased and RER was greatly increased, indicating a high glycolytic metabolism level in BBE-group mice. Consistent with our findings, previous studies showed that inducing fast-twitch myofibers switching by transgenic models or lentivirus treatment significantly improved the muscle performance with an increase in whole-limb grip strength and regulated the glycolytic metabolism with a decrease in O 2 consumption and an increase in RER [5,22]. The above results demonstrated that BBE could increase fast-twitch myofibers proportion and promote myofibers type reprogramming.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, consistent with these findings, the oxygen consumption was markedly decreased and RER was greatly increased, indicating a high glycolytic metabolism level in BBE-group mice. Consistent with our findings, previous studies showed that inducing fast-twitch myofibers switching by transgenic models or lentivirus treatment significantly improved the muscle performance with an increase in whole-limb grip strength and regulated the glycolytic metabolism with a decrease in O 2 consumption and an increase in RER [5,22]. The above results demonstrated that BBE could increase fast-twitch myofibers proportion and promote myofibers type reprogramming.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest bayberry extract shows great potential in regulating glucose metabolism and homeostasis. Taken from the growing body of evidence indicating a strong correlation between fast-twitch myofiber and the regulation of glucose metabolism and homeostasis together [ 13 , 22 , 23 ], bayberry is likely to have influence on the fast-twitch myofiber. Nevertheless, the impact of bayberry extract on the composition of skeletal myofibers is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, oxidative muscle fibers, comprising types I and IIa, display elevated levels of oxidative metabolic enzymes accompanied by increased mitochondrial activity. Glycolytic muscle fibers, particularly type IIb, demonstrate a reduced abundance of mitochondria and heightened activity of the glycolytic enzyme LDH. , Muscle fibers can undergo interconversion in response to physiological and nutritional factors. Patients with OSA exhibit abnormal genioglossus structure and function, characterized by higher than normal proportions of type II fibers and decreased fatigue resistance …”
Section: Introductionmentioning
confidence: 99%
“…In the case of obesity, evidence indicates that obese individuals had increased fast-twitch fibers [ 14 ]. However, the distribution of different fiber types exhibits spatial specificity, but most studies analyze local areas rather than the entire cross-section of fibers [ 15 18 ]. Currently, it remains unclear whether the changes in fiber types are consistent under different physiological and pathological conditions, and the trend of these changes is also unclear.…”
Section: Introductionmentioning
confidence: 99%